2010
DOI: 10.1007/s11244-010-9496-6
|View full text |Cite
|
Sign up to set email alerts
|

Pt and/or Pd Supported/Incorporated Catalyst on Perovskite-Type Oxide for Water Gas Shift Reaction

Abstract: Catalytic properties of Pd and/or Pt supported/ incorporated on/in perovskite-type oxides for water gas shift (WGS) reaction have been investigated. We found that the dominant reaction mechanism over these catalysts was redox mechanism by CO and steam, and their redox properties were controllable by the bulk structure of perovskite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The density of surface oxygen vacancies is about 10-15 % for the two [10,47]. Similarly, we consider oxygen vacancies of nonstoichiometric MnO 1-x as sites for dissociating H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…The density of surface oxygen vacancies is about 10-15 % for the two [10,47]. Similarly, we consider oxygen vacancies of nonstoichiometric MnO 1-x as sites for dissociating H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, perovskite-type oxide (LaCoO 3 ) showed high activity for WGS reaction [7,18]. For that reason, LaCoO 3 was chosen as a perovskite oxide support in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For that reason, LaCoO 3 was chosen as a perovskite oxide support in this study. The preparation method of LaCoO 3 was described elsewhere [7,18]. In the case of iron oxide, a commercial Fe 2 O 3 (Kanto Chemical Co. Inc.) and precipitated Fe 2 O 3 were used.…”
Section: Methodsmentioning
confidence: 99%
“…The loading of a precious metal promoted the ability of releasing the lattice oxygen, and such promotion resulted in an increased WGS performance [23,24]. In order to enhance the WGS activity of the structured catalyst, the LaCoO 3 catalyst supported Pd component was prepared and was its performance investigated.…”
Section: Wgs Performance Of Structured Lacoo 3 and Pd Supported Catalystmentioning
confidence: 99%
“…A preliminary study showed that the reduction temperature of the catalyst could influence the catalytic performance of the WGS reaction [23,24]. A precious metal supported on a perovskite-type oxide has the unique property; the reduction temperature of the perovskite-type oxide is significantly reduced by supporting novel metals such as platinum (Pt) and palladium (Pd).…”
Section: Introductionmentioning
confidence: 99%